Analysis of the Needs for CIMATIK (Interactive Mathematics Canva) Media Based on Problem-Based Learning with a Deep Learning Approach to Enhance Students’ Mathematical Connection Ability - Enung Yunita; Mimih Aminah; Neneng Tita Rosita (MASI Mandiri Edukasi, 2026)
Students’ mathematical connection abilities remain relatively low, while the availability of interactive learning media that effectively support problem-solving and deep conceptual understanding is still limited. This study aims to analyze the need for developing CIMATIK (Canva Interactive Mathematics) media based on Problem-Based Learning (PBL) integrated with a Deep Learning approach to enhance students’ mathematical connection skills. The research employed a needs analysis method involving questionnaires, interviews, and document studies conducted with teachers and students. The analysis focused on the urgency of interactive digital media, the characteristics of mathematics learning materials, students’ and teachers’ preferences in technology use, and the suitability of Canva features for developing PBL-oriented instructional media. The results indicate a strong need for user-friendly, visually engaging, and interactive digital media that facilitate concept exploration and meaningful learning experiences. The Deep Learning approach is considered relevant in supporting higher-order thinking skills, strengthening conceptual understanding, and enhancing inter-concept connections through contextual PBL scenarios. CIMATIK media is perceived to have significant potential to increase student engagement, improve conceptual representation, and enhance mathematical connection abilities. These findings provide a foundational basis for developing an effective CIMATIK prototype that aligns with the demands of 21st-century mathematics learning.